Role of miR-27a, miR-181a and miR-20b in gastric cancer hypoxia-induced chemoresistance. Issue 4 (2nd April 2016) - Danza, Katia; Silvestris, Nicola; Simone, Giovanni; Signorile, Michele; Saragoni, Luca; Brunetti, Oronzo; Monti, Manlio; Mazzotta, Annalisa; De Summa, Simona; Mangia, Anita; Tommasi, Stefania
ABSTRACT: Despite the search for new therapeutic strategies for gastric cancer (GC), there is much evidence of progression due to resistance to chemotherapy. Multidrug resistance (MDR) is the ability of cancer cells to survive after exposure to chemotherapeutic agents. The involvement of miRNAs in the development of MDR has been well described but miRNAs able to modulate the sensitivity to chemotherapy by regulating hypoxia signaling pathways have not yet been fully addressed in GC. Our aim was to analyze miR-20b, miR-27a and miR-181a expression with respect to (epirubicin/oxaliplatin/capecitabine (EOX)) chemotherapy regimen in a set of GC patients, in order to investigate whether miRNAs deregulation may influence GC MDR also via hypoxia signaling modulation. Cancer biopsy were obtained from 21 untreated HER2 negative advanced GC patients, retrospectively analyzed. All patients received a first-line chemotherapy (EOX) regimen. MirWalk database was used to identify miR-27a, miR-181a and miR-20b target genes. The expression of miRNAs and of HIPK2, HIF1A and MDR1 genes were detected by real-time PCR. HIPK2 localization was assessed by immunohistochemistry. Our data showed the down-regulation of miR-20b, miR-27a, miR-181a concomitantly to higher levels of MDR1, HIF1A and HIPK2 genes in GC patients with a progressive disease respect to those with a disease control rate. Moreover, immunohistochemistry assay highlighted a higher cytoplasmic HIPK2 staining, suggesting a different role for it. We showed that aberrant expression of miR-20b, miR27a and miR-181a was associated with chemotherapeutic response in GC through HIF1A, MDR1 and HIPK2 genes modulation, suggesting a possible novel therapeutic strategy.